Effect of Cigarette Smoking on Serum Homocysteine and Vitamin B12 Levels in Apparently Healthy Male Smokers - Dhar, Ujjal Chandra; Sarker, Beethi; Rahman, AFSM Shazedur; Siddika, Syeda Tasfia; Progga, Tasnim Tabassum (Mugda Medical College Journal, 2025)
A cross-sectional, analytical study was carried out, between July 2019 and June 2020, to evaluate the effect of cigarette smoking on serum homocysteine and vitamin B12 levels in apparently healthy male smokers. A total of 90 male subjects were included in this study. Among them, 60 apparently healthy male smoker subjects aged between 20 and 60 years were considered as study group (group A); smokers were subdivided into two groups according to the pack-years of smoking history: group A1 (smokers with 5-10 pack-years of smoking history) and group A2 (smokers with >10 pack-years of smoking history). Another 30 apparently healthy non-smoker male subjects (age and BMI matched) were considered as comparison group (group B). All the subjects were selected from the hospital staff members of Mitford hospital and Bangabandhu Sheikh Mujib Medical University (BSMMU) hospital, Dhaka, Bangladesh, and also some from personal contact. All biochemical tests were performed in the Department of Biochemistry and Molecular Biology of Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh. The study parameters were serum homocysteine, and serum vitamin B12. Serum homocysteine level was found significantly higher among smokers compared to non-smokers (p<0.001), while vitamin B12 level was found significantly lower among smokers (p<0.001). Moreover, these changes were more profound in the smokers with >10 pack-year of smoking history. Beside this, serum homocysteine level was positively correlated (r= +0.948) with pack-year of smoking history (p<0.001),. while vitamin B12 level was negatively correlated (r= –0.844) with pack-year of smoking history (p<0.001). Our study revealed that long term smoking has significant effects on serum homocysteine and vitamin B12 levels. Mugda Med Coll J. 2025; 8(2): 101-106